Incidence of Breakthrough Reaction in Patients with Prior Acute Allergic-Like Reactions to Iodinated Contrast Media according to the Administration Route - Kim, Yeon Soo; Choi, Young Hun; Cho, Yeon Jin; Lee, Seunghyun; Yoon, Soon Ho; Park, Chang Min; Kang, Hye Ryun (Korean journal of radiology, 2018)
This study assessed the risk of acute allergic-like reactions (AARs) after extravascular administration of iodinated contrast media (ICM) in at-risk patients compared with that after intravascular ICM administration. From July 2012 to January 2016, 264 patients with a history of moderate or severe reactions to ICM, with re-exposure to ICM intravascularly or extravascularly were included. The incidence of recurrent AARs after ICM re-exposure were assessed according to the administration routes by reviewing electronic medical records and comparison between the two routes. Among 264 patients, 244 patients had been subsequently exposed to ICM intravascularly, 7 patients via an extravascular route and 13 patients with dual re-exposure. Of 257 patients with intravascular ICM re-exposure, 87 (33.9%) had mild to severe recurrent AARs and 143 (19.5%) cases of recurrent AARs occurred among 733 cases of intravascular ICM re-exposure on a case-by-case basis. However, there was no case of recurrent ARR after extravascular administration of ICM in 20 patients (45 cases) with ICM administrated extravascularly. For high-risk patients with a history of moderate or severe reactions to ICM, AARs upon extravascular administration of ICM are significantly infrequent compared with intravascular ICM administration.